Penyuluhan Kesehatan Tentang “Waspada! Penyakit Kulit Menular: Sehat Bersama, Hidup Nyaman” Di SMK IT Subulussalam Samarinda - Tri Riski Amalia; Muhammad Nahrawi Udharaja; Barolym Tri Pamungkas (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Infectious skin diseases are conditions where the skin is infected by bacteria, viruses, fungi, or parasites that can be transmitted from one individual to another. These infections not only cause physical discomfort but can also lead to serious complications if left untreated. The aim of this health promotion is to increase public understanding of the causes, symptoms, transmission, prevention, and treatment of infectious skin diseases. The activity methodology is a one-group pre-post design by measuring knowledge before and after the counseling. The instrument used is a knowledge questionnaire related to the causes, symptoms, transmission, prevention, and treatment of infectious skin diseases. The results achieved after conducting counseling on "Beware! Infectious Skin Diseases: Healthy Together, Live Comfortably" at SMK IT Subulussalam experienced an increase from 58% to 74%.